2020
DOI: 10.4330/wjc.v12.i11.526
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial progenitor cells mobilization after maximal exercise according to heart failure severity

Abstract: BACKGROUND Vascular endothelial dysfunction is an underlying pathophysiological feature of chronic heart failure (CHF). Patients with CHF are characterized by impaired vasodilation and inflammation of the vascular endothelium. They also have low levels of endothelial progenitor cells (EPCs). EPCs are bone marrow derived cells involved in endothelium regeneration, homeostasis, and neovascularization. Exercise has been shown to improve vasodilation and stimulate the mobilization of EPCs in healthy p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 34 publications
0
24
0
1
Order By: Relevance
“…Fifteen clinical trials examined the acute effects to exercise (Adams et al 2004 ; Shaffer et al 2006 ; Van Craenenbroeck et al 2009 ; Van Craenenbroeck et al 2010a ; Sandri et al 2011 ; Van Craenenbroeck et al 2011 ; Rummens et al 2012 ; Scalone et al 2013 ; Kazmierski et al 2015 ; Rocha et al 2015 ; West et al 2015 ; Lutz et al 2016 ; Waclawovsky et al 2016 ; Gevaert et al 2019 ; Kourek et al 2020b ) (Table 1 ). Thirteen trials included independent groups before and after (Adams et al 2004 ; Shaffer et al 2006 ; Van Craenenbroeck et al 2009 ; Van Craenenbroeck et al 2010a ; Van Craenenbroeck et al 2011 ; Rummens et al 2012 ; Scalone et al 2013 ; Kazmierski et al 2015 ; Rocha et al 2015 ; West et al 2015 ; Lutz et al 2016 ; Gevaert et al 2019 ; Kourek et al 2020b ), one was a single arm trial (Sandri et al 2011 ) and another one a randomised cross over trial (Waclawovsky et al 2016 ). Across the 15 included trials (649 participants), 13 reported percentages of male and female distribution (Van Craenenbroeck et al 2009 ; Van Craenenbroeck et al 2010a ; Sandri et al 2011 ; Van Craenenbroeck et al 2011 ; Rummens et al 2012 ; Scalone et al 2013 ; Kazmierski et al 2015 ; Rocha et al 2015 ; West et al 2015 ; Lutz et al 2016 ; Waclawovsky et al 2016 ; Gevaert et al 2019 ; Kourek et al 2020b ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fifteen clinical trials examined the acute effects to exercise (Adams et al 2004 ; Shaffer et al 2006 ; Van Craenenbroeck et al 2009 ; Van Craenenbroeck et al 2010a ; Sandri et al 2011 ; Van Craenenbroeck et al 2011 ; Rummens et al 2012 ; Scalone et al 2013 ; Kazmierski et al 2015 ; Rocha et al 2015 ; West et al 2015 ; Lutz et al 2016 ; Waclawovsky et al 2016 ; Gevaert et al 2019 ; Kourek et al 2020b ) (Table 1 ). Thirteen trials included independent groups before and after (Adams et al 2004 ; Shaffer et al 2006 ; Van Craenenbroeck et al 2009 ; Van Craenenbroeck et al 2010a ; Van Craenenbroeck et al 2011 ; Rummens et al 2012 ; Scalone et al 2013 ; Kazmierski et al 2015 ; Rocha et al 2015 ; West et al 2015 ; Lutz et al 2016 ; Gevaert et al 2019 ; Kourek et al 2020b ), one was a single arm trial (Sandri et al 2011 ) and another one a randomised cross over trial (Waclawovsky et al 2016 ). Across the 15 included trials (649 participants), 13 reported percentages of male and female distribution (Van Craenenbroeck et al 2009 ; Van Craenenbroeck et al 2010a ; Sandri et al 2011 ; Van Craenenbroeck et al 2011 ; Rummens et al 2012 ; Scalone et al 2013 ; Kazmierski et al 2015 ; Rocha et al 2015 ; West et al 2015 ; Lutz et al 2016 ; Waclawovsky et al 2016 ; Gevaert et al 2019 ; Kourek et al 2020b ).…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen trials included independent groups before and after (Adams et al 2004 ; Shaffer et al 2006 ; Van Craenenbroeck et al 2009 ; Van Craenenbroeck et al 2010a ; Van Craenenbroeck et al 2011 ; Rummens et al 2012 ; Scalone et al 2013 ; Kazmierski et al 2015 ; Rocha et al 2015 ; West et al 2015 ; Lutz et al 2016 ; Gevaert et al 2019 ; Kourek et al 2020b ), one was a single arm trial (Sandri et al 2011 ) and another one a randomised cross over trial (Waclawovsky et al 2016 ). Across the 15 included trials (649 participants), 13 reported percentages of male and female distribution (Van Craenenbroeck et al 2009 ; Van Craenenbroeck et al 2010a ; Sandri et al 2011 ; Van Craenenbroeck et al 2011 ; Rummens et al 2012 ; Scalone et al 2013 ; Kazmierski et al 2015 ; Rocha et al 2015 ; West et al 2015 ; Lutz et al 2016 ; Waclawovsky et al 2016 ; Gevaert et al 2019 ; Kourek et al 2020b ). Across these 13 trials (573 participants), 435 were males (75.9%) and 138 were females (24.1%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No espaço de tempo delimitado para a realização deste estudo (2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019)(2020) No estudo de Kourek et al (2020), buscaram avaliar quantificar e comparar a mobilização aguda das CPE após exercício máximo em pacientes com insuficiência cardíaca crônica (ICC). Para isso, selecionaram 49 pacientes consecutivos com ICC estável e um fração de ejeção reduzida ou média (EF) que foram submetidos a uma única sessão de teste de exercício cardiopulmonar máximo (CPET).…”
Section: Resultsunclassified
“…We extended previous findings by showing that a single bout of maximal exercise, as well as many bouts organized as an exercise training program, stimulates the mobilization of EPCs and CECs from the bone marrow in patients with chronic HF[ 8 , 10 ]. This beneficial effect of exercise seems to be similar in chronic HF patients of different severity[ 9 ].…”
Section: The Effect Of Exercise Training In the Cardiomyocytes Vascular Endothelial Function And Skeletal Musclesmentioning
confidence: 99%